SAT0013 Juvenile Idiopathic Arthritis Association of PTPN22 rs2476601 SNP Is Specific To Females in A Greek Population. (15th July 2016) - Goulielmos, G.N.; Chiaroni-Clarke, R.; Dimopoulou, D.G.; Zervou, M.I.; Trachana, M.; Pratsidou-Gertsi, P.; Myrthianou, E.; Garyfallos, A.; Ellis, J.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is an autoimmune disease characterized by persistent chronic arthritis [1] and is believed to be influenced by both genetic and environmental factors. PTPN22 single nucleotide polymorphism (SNP) rs2476601 has been recently reported in an Australian study to be restricted to females and to not be observed in males [2]. Objectives: Considering that a significant source of inconsistency amongst the literature on autoimmune disease susceptibility genes stems from an inability to replicate genetic findings across different racial or ethnic groups, we attempted to confirm the female-specific association of rs2476601 in a homogeneous Greek population. Methods: The sample set consisted of 128 (70.3% female) Caucasian JIA patients and 221 (28.1% female) healthy controls from Northern Greece. Genotyping for the PTPN22 rs2476601 ( Xcm I) was performed by restriction fragment length polymorphism (RFLP) analysis [3]. Logistic regression or the Gart (Woolf) method were used to estimate ORs and 95% CIs. Analyses were performed using Stata v13 (StataCorp, College Station, TX, USA). Results: The rs2476601 was genotyped in 128 Caucasian JIA patientsand 221 healthy controls from Northern Greece. Overall, PTPN22 was associated with increased risk of JIA in this Greek sample (OR =2.3, 95% CI 1.1 – 5.1, p=0.038). Sex-stratified analyses showed that, once again, the risk association was restricted to females (Female: OR =19.9, 95% CI 1.2 – 342, p=0.0016; Male: OR =1.1, 95% CI 0.3 – 3.1, p=0.94) confirming the prior findings. Given that the sex bias differs by JIA subtype, ideally we would have liked to test for these associations in individual subtypes; however, small sample size prevented us from performing these analyses with any statistical certainty. Conclusions: This data demonstrated that the sex-specific pattern of association detected is broadly applicable to different populations, and provided further impetus to undertake studies to understand the crucial role of rs2476601 in the mechanisms leading to disease's development preferentially in females. Our work is of interest given the importance of comparative studies in populations of differing ethnic and/or racial origin in any attempt to conclusively define the genetic architecture of JIA and the magnitude of the effects of specific risk alleles globally. References: Ravelli and Martini (2007). Lancet 369:767–778. Chiaroni-Clarke et al (2015). Genes Immun. 16:495–498. Eliopoulos et al (2010). Lupus 105:501–506. Disclosure of Interest: None declared